DETERMINAN PERSISTENSI LABA PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Rizky Kurniawan; Natali Yustisia (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2021)
The purpose of this study is to analyze the effect of cash flow volatility, sales volatility, debt level and firm size on earnings persistence. The population of this study are manufacturing companies listed at Indonesia Stock Exchange for the 2017-2020 period. The sampling method used in this research is purposive sampling technique. The number of sample were 34 companies. The analysis technique used in this research is panel data regression with EViews 9 software. The results of the study using the random effects model show that cash flow volatility and sales volatility have no significant effect on earnings persistence. The level of debt has a significant negative effect on earnings persistence, while firm size has a significant positive effect on earnings persistence.